Synergistic and antagonistic effect of chain lengths below and above critical value on polyelectrolyte complex. (24th October 2019) - Yin, Dongxiao; Pan, Wei; Liang, Dehai
Abstract: The effects of chain length and polydispersity on polyelectrolyte complexes (PEC) have not been fully clarified. In this work, we chose oligonucleotide and oligolysine, both of which have uniform length, and studied the chain length effect on their complex by time-resolved laser light scattering and atomic force microscopy. Results show that the chain length of oligolysine has to reach a critical value for the occurrence of complexation with 21 bp oligonucleotides, suggesting that PEC is an all-or-non process. However, the oligolysine with the chain length below critical value still plays a role if it is mixed with other oligolysine whose chain length is above the critical value. If oligonucleotide is in excess, the combination of oligolysines with chain lengths below and above critical value exhibits synergistic effect to enhance the PEC formation, while they exhibit antagonistic effect to deteriorate the PEC formation if oligolysine is in excess. Our study not only gains insight in the mechanism of PEC by polydispersed samples, but also helps to design and fabricate complexes with desirable structure and kinetics by combining polyelectrolytes with different chain lengths. Graphical abstract: Image 1 Highlights: A critical chain length (lc ) exists, below which no PEC forms. The lc is dependent on polymer type and PEC preparation conditions. Synergistic effect is observed if oppositely charged polyelectrolyte is in excess. Antagonistic effect is observed if polyelectrolyte of same charge is in excess.